THE INFLUENCE OF WORK-LIFE BALANCE ON THE PRODUCTIVITY OF MEDICAL PERSONNEL AT DR. MINTOHARDJO NAVAL HOSPITAL - Lelyana, Nora; Sarjito, Aris (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Maintaining a balance between work and personal life (work-life balance) is a significant challenge for healthcare professionals, especially in hospitals with shift-based schedules and high workloads. This imbalance can lead to stress, burnout, and reduced productivity, ultimately affecting the quality of patient care. This study aims to explore how work-life balance impacts the productivity of medical personnel at Dr. Mintoharjo Naval Hospital. A qualitative approach was employed, using secondary data analysis drawn from academic journals, research reports, and institutional publications to identify key influencing factors. Findings indicate that excessive workload, lack of social and institutional support, and limited access to mental health resources are major barriers to achieving balance. However, hospital policies such as flexible work schedules, psychological support services, and the integration of technology in administrative management have been shown to improve medical personnel’s well-being. In conclusion, hospitals that prioritize work-life balance for their healthcare workers not only enhance their productivity but also improve the quality of healthcare services provided to patients.